An observational study of meconium aspiration syndrome and its immediate outcome with relation to thick and thin meconium stained amniotic fluid - Kumar, Sushant; Akhouri, Minni Rani (International Journal of Contemporary Pediatrics, 2018)
Background: Meconium-stained amniotic fluid (MSAF) accounts for approximately 10-15% of live births and Meconium aspiration syndrome occurs in 5% among infants born through MSAF. The purpose of this study was to evaluate the outcome in neonates with meconium aspiration syndrome with regard to thin and thick meconium. Methods: A prospective cohort study of inborn neonates was done from April 2016 to August 2017 admitted in neonatal intensive care unit, Department of Paediatrics and Neonatology, RIMS, Ranchi after obtaining written informed consent from the parents or guardian and diagnosis of MAS was made depending on the clinical criteria and its clinical outcome was observed. MAS babies were studied on the basis of thin and thick meconium stained amniotic fluid. Results: The mean birth weight in thin meconium was 2760±394. The mean APGAR score in thin meconium at 1 minute (3.57±1.01) and 5 minutes (5.57±1.62) was significantly more than thick meconium. The mode of delivery in thin meconium was commonly by cesarean section (76.9%). There was need for resuscitation in 46.1% in thin meconium neonates which was significantly higher than neonates born with thick meconium 6.6% (P value 0.000). The most common complication in thin meconium was birth asphyxia (69.2%), followed by ARF and septicemia. Death was significantly higher in neonates born with thin meconium (69.2%)as compared to thick (20%) with P value of 0.000 Conclusions: Amniotic fluid with thin meconium may cause more respiratory and other complications in neonates than amniotic fluid with thick meconium. Hence proper diagnosis and timely intervention can reduce the morbidity and mortality in neonates with meconium aspiration syndrome.